2008
DOI: 10.1007/s10350-008-9284-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Endoanal Ultrasound for Fistula-in-Ano: A Retrospective Analysis

Abstract: The findings and accuracy of preoperative endoanal ultrasound did not influence postoperative outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 14 publications
1
18
0
1
Order By: Relevance
“…The accuracy rate of EAUS is estimated as 80%-89% for delineating fistula tract, 91% for internal opening. EAUS is particularly accurate in identifying horseshoe abscess and its extension [5,[15][16][17][18]. Threedimensional ultrasound techniques provide even better imaging quality and orientation, with an accuracy rate comparable to that of MRI, especially for complex anal fistula [12,13,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The accuracy rate of EAUS is estimated as 80%-89% for delineating fistula tract, 91% for internal opening. EAUS is particularly accurate in identifying horseshoe abscess and its extension [5,[15][16][17][18]. Threedimensional ultrasound techniques provide even better imaging quality and orientation, with an accuracy rate comparable to that of MRI, especially for complex anal fistula [12,13,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is a financial cost of the EAUS examination and discomfort experienced by some patients, especially when hydrogen peroxide injection is performed [7,23]. Therefore, the clinical utility of preoperative EAUS has been questioned [5,6]. In contrast Ratto et al [18] reported that preoperative EAUS led to a high rate of operative success as well as a low frequency of anal incontinence, suggesting that the use of EAUS improves postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Die Korrelation zwischen endoanalem Ultraschall und der intraoperativen klinischen Untersuchung liegt bei über 90% [37,155,167,218]. Eine Beeinflussung des operativen Vorgehens in erster Linie im Sinne eines mehr konservativen Vorgehens wird von Lindsey et al [159] bei 38% der Patienten beschrieben, während Weisman et al [299] keine Beeinflussung des perioperativen Verlaufes durch die Endosonographie nachweisen konnten. Subasighe et al [262] sehen die Bedeutung der Endosonographie v. a. im Nachweis von nichtdrainierten Sekretverhalten vor einer Fisteloperation.…”
Section: Weiterführende Diagnostikunclassified